2008
DOI: 10.1242/jcs.023812
|View full text |Cite
|
Sign up to set email alerts
|

Slk1 is a meiosis-specific Sid2-related kinase that coordinates meiotic nuclear division with growth of the forespore membrane

Abstract: Resultsslk1 is a meiosis-specific sid2 paralogue The slk1 (mug27) gene was identified in a large-scale-deletion screening of meiotically upregulated genes (Martin-Castellanos et al., 2005). Viable mug mutants (167 in total) were systematically Septation and spore formation in fission yeast are compartmentalization processes that occur during the mitotic and meiotic cycles, and that are regulated by the septation initiation network (SIN). In mitosis, activation of Sid2 protein kinase transduces the signal from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 43 publications
(49 reference statements)
5
18
0
Order By: Relevance
“…Because mug27-D cells produce small spores, whereas 3289 dma1 in spore formation dma1-D cells produce large spores, we tested whether the steadystate levels of mug27p were affected in dma1-D. We observed that mug27p levels peaked at the transition from meiosis I to meiosis II and then declined at the time of spore formation (Fig. 8A), consistent with previous studies (Ohtaka et al, 2008;Perez-Hidalgo et al, 2008;Yan et al, 2008). By contrast, in dma1-D meiosis, mug27p persisted beyond the onset of meiosis II (Fig.…”
Section: Dma1p Is Required For Timely Elimination Of Mug27psupporting
confidence: 86%
See 1 more Smart Citation
“…Because mug27-D cells produce small spores, whereas 3289 dma1 in spore formation dma1-D cells produce large spores, we tested whether the steadystate levels of mug27p were affected in dma1-D. We observed that mug27p levels peaked at the transition from meiosis I to meiosis II and then declined at the time of spore formation (Fig. 8A), consistent with previous studies (Ohtaka et al, 2008;Perez-Hidalgo et al, 2008;Yan et al, 2008). By contrast, in dma1-D meiosis, mug27p persisted beyond the onset of meiosis II (Fig.…”
Section: Dma1p Is Required For Timely Elimination Of Mug27psupporting
confidence: 86%
“…A sid2p-related kinase called mug27 (also known as ppk35 or slk1; hereafter called mug27) is expressed during meiosis (Ohtaka et al, 2008;Perez-Hidalgo et al, 2008;Yan et al, 2008). A sid2-250 mug27-D double mutant makes no spores at all, indicating that the two kinases cooperate.…”
Section: The Sin and Its Regulatorsmentioning
confidence: 99%
“…Slk1p has been identified as the product of the mug27 gene (meiotic up-regulated gene-27) from a microarray based analysis of genes expressed during meiosis, and its expression has not been detected in mitotically growing vegetative cells (Martin-Castellanos et al, 2005). Slk1p has been independently characterized by two other research groups recently and these authors arrive largely at similar conclusions (Ohtaka et al, 2008;Perez-Hidalgo et al, 2008).…”
Section: The Protein Kinases Slk1p and Sid2p Localize To The Spb Durimentioning
confidence: 98%
“…Slk1p has been identified as the product of the mug27 gene (meiotic up-regulated gene-27) from a microarray based analysis of genes expressed during meiosis, and its expression has not been detected in mitotically growing vegetative cells (Martin-Castellanos et al, 2005). Slk1p has been independently characterized by two other research groups recently and these authors arrive largely at similar conclusions (Ohtaka et al, 2008;Perez-Hidalgo et al, 2008).Although the regions of high similarity between Slk1p and Sid2p lie in the protein kinase domain (ϳ51% identity), the nonkinase domains are also related, in that the amino acids upstream of the kinase domain exhibit 18% identity, whereas those downstream of the kinase domain exhibit 28% identity. Slk1p, like Sid2p, contains activatory phosphorylation sites within the kinase domain (serine 356) and the nonkinase domain (threonine 537).…”
mentioning
confidence: 93%
“…Time course observations revealed that this "lysed phenotype" was already apparent 14 h after meiotic induction, and a subsequent delay in meiotic progression when the meiotic recombination checkpoint is activated. 6 The meiosis-specific Slk1 (Mug27) kinase, a paralog of septation initiation kinase Sid2, regulates FSM assembly and sporulation. [7][8][9] We previously reported that Spo5 protein levels during meiosis are somehow regulated by Spo5 phosphorylation-dependent proteolysis.…”
Section: Spo5 Phosphorylation Is Essential For Its Own Timely Degradamentioning
confidence: 99%